2022
DOI: 10.7759/cureus.21965
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Depression and Related Factors During the COVID-19 Pandemic Among the General Population of the Jazan Region of Saudi Arabia

Abstract: BackgroundThis study examines the rates of depression associated with the COVID-19 pandemic along with mitigation measures such as lockdown and quarantine in the population of the Jazan region in Saudi Arabia. The Kingdom of Saudi Arabia (KSA) began mitigation measures before the first case appeared on March 2, 2020, disrupting daily life in a culture that is centered on family life. We sought to assess the psychological impacts of the pandemic on this culturally unique region to see if it affected as many as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Contrary to some reports, our data did not find gender, EF group, DM, or HTN to exhibit strong predictive power for in-hospital mortality among COVID-19 patients [ 42 , 43 , 48 , 49 ]. These findings align with the growing number of studies indicating that the relationships between these variables and COVID-19 outcomes are complex and multifactorial.…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to some reports, our data did not find gender, EF group, DM, or HTN to exhibit strong predictive power for in-hospital mortality among COVID-19 patients [ 42 , 43 , 48 , 49 ]. These findings align with the growing number of studies indicating that the relationships between these variables and COVID-19 outcomes are complex and multifactorial.…”
Section: Discussioncontrasting
confidence: 99%
“…of which 31%, 13.4%, 4.4%, and 1% were mild, moderate, moderate-severe, and severe, respectively [28]. However, the prevalence of depression in our study was higher than that reported among the general population in the Jazan region in Saudi Arabia during the COVID-19 pandemic, with a rate of nearly 26% [29] and higher than that reported by Alamri et al, in which 28.9% of the general Saudi population reported experiencing any depressive symptoms, of which 11.8% were mild, 10.1% were moderate, and 7% were severe [30].…”
Section: Plos Onecontrasting
confidence: 73%
“…Interestingly, a study done in Jazan city found that 26% of the participants were depressed and the presence of chronic diseases and female gender were risk factors for this negative symptom. 19 …”
Section: Introductionmentioning
confidence: 99%